2013
DOI: 10.1530/joe-13-0045
|View full text |Cite
|
Sign up to set email alerts
|

Multiple signaling pathways mediate ghrelin-induced proliferation of hippocampal neural stem cells

Abstract: Ghrelin, an endogenous ligand for the GH secretagogue receptor (GHS-R) receptor 1a (GHS-R1a), has been implicated in several physiologic processes involving the hippocampus. The aim of this study was to investigate the molecular mechanisms of ghrelin-stimulated neurogenesis using cultured adult rat hippocampal neural stem cells (NSCs). The expression of GHS-R1a was detected in hippocampal NSCs, as assessed by western blot analysis and immunocytochemistry. Ghrelin treatment increased the proliferation of cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 56 publications
3
44
1
Order By: Relevance
“…That effect might be due to suppression of mTOR pathway, modulated by sulfite via tuberin activation, by ghrelin, which also supports the increase of cell proliferation by ghrelin administration in our previous study (24). Similarly, a study reported that mTOR/P70S6k signaling pathway mediated ghrelin-induced proliferation of neural stem cells (39).…”
Section: P-tuberinsupporting
confidence: 87%
“…That effect might be due to suppression of mTOR pathway, modulated by sulfite via tuberin activation, by ghrelin, which also supports the increase of cell proliferation by ghrelin administration in our previous study (24). Similarly, a study reported that mTOR/P70S6k signaling pathway mediated ghrelin-induced proliferation of neural stem cells (39).…”
Section: P-tuberinsupporting
confidence: 87%
“…Additionally, in our recent report [7], we found that mice with targeted disruption of the ghrelin gene showed a decreased number of progenitor cells in the dentate gyrus (DG) of the hippocampus, while ghrelin replacement restored progenitor cell numbers to those of wild-type (WT) controls. Proliferative effect of ghrelin on hippocampal progenitor cells seems to be mediated through the activation of its receptor because GHS-R1a antagonist completely blocked the effect of ghrelin in vitro [8]. Collectively, these findings suggest that ghrelin may play an important role in adult hippocampal neurogenesis.…”
mentioning
confidence: 75%
“…Since ghrelin leads to neuropeptide Y and GABA release in the hypothalamus, it may have a similar action in the hippocampus [214]. Another possibility is that ghrelin induces the proliferation of hippocampal neural stem cells [222]. Alternatively, it acts as an anti-inflammatory agent, as demonstrated in the periphery [223].…”
Section: Ghrelinmentioning
confidence: 99%